2000
DOI: 10.1002/1521-3773(20001201)39:23<4337::aid-anie4337>3.0.co;2-4
|View full text |Cite
|
Sign up to set email alerts
|

Selective Trimerization ofα-Olefins with Triazacyclohexane Complexes of Chromium as Catalysts

Abstract: Olefin trimers can be prepared selectively from α‐olefins with n‐alkyl‐substituted triazacyclohexane–CrCl3 complexes as catalysts in the presence of methyaluminoxane (MAO).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
83
0
3

Year Published

2001
2001
2011
2011

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 166 publications
(88 citation statements)
references
References 14 publications
2
83
0
3
Order By: Relevance
“…Kö hn et al [50] subsequently showed that these triazacyclohexane complexes of Cr(III) were capable of trimerising higher alpha olefins such as propene, 1-hexene and styrene. Up until this time no other trimerisation catalysts were shown to be capable of this transformation with higher olefin substrates.…”
Section: Ligands Based On Nitrogen Donorsmentioning
confidence: 99%
“…Kö hn et al [50] subsequently showed that these triazacyclohexane complexes of Cr(III) were capable of trimerising higher alpha olefins such as propene, 1-hexene and styrene. Up until this time no other trimerisation catalysts were shown to be capable of this transformation with higher olefin substrates.…”
Section: Ligands Based On Nitrogen Donorsmentioning
confidence: 99%
“…Reactions carried out beyond 1 min showed a gradual decrease in the catalytic activities. For example, catalyst system 2b/ EtAlCl 2 afforded 7.6, 7.1, 6.2 and 4.2 Â 10 2 g mol À1 Pd h À1 after 1, 5, 15, and 30 min (Table 3, entries 5, 6,7,8) respectively. In addition, increasing the reaction time from 1 to 30 min led to a slight reduction in the amount of C 4 (e.g.…”
Section: The Influence Of Reaction Timementioning
confidence: 99%
“…It is well known that heterogeneous catalysts result in multisite active species in olefin polymerization [5][6][7], however, homogeneous catalysts provide the opportunity in understanding the active species and polymerization/oligomerization mechanism which might be helpful in designing advanced catalysts [8][9][10]. On the other hand, chromium catalysts are still being the only practicing catalysts for the on-purpose process for ethylene trimerization or tetramerization [11][12][13][14][15][16][17][18][19]. Therefore it has attracted for designing homogeneous catalysts of chromium complexes through developing multidentate ligands, such as N^N (iminopyrrolide [20,21], b-diketiminate [21][22][23][24][25], bis(phosphoranimine)methanide [26] and bis(imidazole) [27,28]), N^O [29][30][31], P^P or P^N^P [32][33][34][35][36][37][38][39], P^P^P [40], N^P^N [41], S^N^S [34,35,42], N^S^N [43], C^N^C [44], N^N^O [4...…”
Section: Introductionmentioning
confidence: 99%